Evaluation of lethality and cytotoxic effects induced by Naja ashei (large brown spitting cobra) venom and the envenomation-neutralizing efficacy of selected commercial antivenoms in Kenya - Ernest Z. Manson; Mutinda C. Kyama; Joseph K. Gikunju; Josephine Kimani; James H. Kimotho (Toxicon: X, 2022)
Neutralization of lethality in mice model at the preclinical level has been established by the World Health Organization as the gold standard for the evaluation of antivenom efficacy. The assessment of the neutralization profiles of antivenoms helps to discern the efficacy or otherwise of these antivenoms at neutralizing the toxic effects induced by medically significant snake venoms. However, for many antivenoms, information on their preclinical efficacy remains limited. Therefore, to strengthen global efforts at reducing the impact of snakebite envenoming, the provision of information on the preclinical efficacy of antivenoms, especially in parts of the world where antivenom availability and accessibility is problematic, including sub-Saharan Africa is crucial. This study presents the lethal and toxic activities of N. ashei venom and the neutralizing capacity of two commonly used commercial antivenoms in Kenya; VINS™ and Inoserp™. Median lethal dose (LD50), minimum necrotizing dose (MND) and minimum edema-forming dose (MED) of N. ashei venom as well as the neutralization of these effects were evaluated in mice. The LD50 of N. ashei venom was found to be 4.67 (3.34–6.54) mg/kg while MND and MED were 11.00 μg and 0.80 μg respectively. Both VINS™ and Inoserp™ antivenoms demonstrated capacity to neutralize the lethal and toxic effects induced by Naja ashei venom albeit at varying efficacies. Our results thus confirm the toxic effects of N. ashei venom as previously observed with other Naja sp. venoms and also underscore the relevance of para-specific neutralizing capacity of antivenoms in the design of antivenoms.